PENERAPAN BAGI HASIL DALAM PEMBIAYAAN MUDHARABAH DI BANK MUAMALAT TULUNGAGUNG - Bagus Ahmadi; Arif Nur'aini (LPPM STAI Muhammadiyah Probolinggo, 2023)
The banking system has a strategic position as a support for the national economy. In Indonesia there are two banking systems, namely conventional banking systems and Islamic banking. In general, saving in conventional and sharia banking is no different, because both banks are required to follow general banking techniques. However, if analyzed more deeply, there are fundamental differences between the two. The first difference lies in the contract and the second difference in the reward. In banking products for profit-sharing contracts there are two, namely the Mudhorobah contract and the Musyarakah contract. However, mudhorobah contracts are rarely used for transactions in all Islamic banks. Of the products available at Islamic banks, one of them is mudhorobah contract financing in Islamic banking. This study has two problem formulations, namely how the terms and mechanisms of mudharabah financing at Bank Muamalat and how the implementation of mudharabah financing at Bank Muamalat. The purpose of this study is the first, to find out the mechanism and mudharabah transactions at Bank Muamalat Tulungagung, second to find out the implementation of mudharabah financing at Bank Muamalat Tulungagung. By using qualitative research methods, the first type of research, location, second source of data, third data analysis and data collection procedures, fourth technique, fifth data validation, and the sixth research stage. Keywords: application and mudharabah contract